Pengaruh Green Accounting terhadap Nilai Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia pada Tahun 2018-2023 - Putra Nur Kaimuddin; Hariany Idris; Samirah Dunakhir (Lembaga Pengembangan Kinerja Dosen, 2026)
This study focuses on examining the extent to which the implementation of green accounting affects firm value in pharmaceutical companies listed on the Indonesia Stock Exchange during the 2018–2023 period. The variables used include: (1) firm value as the dependent variable (Y), measured using the Price to Book Value (PBV) ratio, and (2) green accounting as the independent variable (X), assessed based on the results of the Corporate Performance Rating Program in Environmental Management (PROPER). The population of this study consists of all pharmaceutical sector issuers listed on the Indonesia Stock Exchange in 2023, totaling 13 companies. From this population, 5 companies were selected as samples using a purposive sampling method based on specific criteria. Data were collected through documentation of the companies’ annual reports and sustainability reports. The data analysis stages included classical assumption tests to ensure the validity of the model, followed by simple linear regression analysis and hypothesis testing using SPSS version 31 software. The data processing results indicate that the green accounting variable has a significance level of < 0.001, which is below the 0.05 threshold, with a calculated t-value of 6.754. This indicates that the implementation of green accounting has a positive and significant effect on firm value. Thus, the first research hypothesis (H1) is accepted.